Rush - Banks, Maya (New York : Berkley Books, 2013)
Gabe is wealthy, powerful, and accustomed to getting anything he wants. Anything-- and anyone. For Gabe, it's one particular fantasy with a woman who was forbidden fruit. Now she's ripe for the picking ... Mia was his best friend's little sister ... but she's not so little any more. Mia knows Gabe is way out of her league, but she's an adult now, and there's no reason not to act on her most secret desires. But she doesn't know how exacting his demands can be ..
"Mature audience"--P. [4] of cover
Keywords: Hotelkeepers -- Fiction; Adultery -- Fiction; Bondage (Sexual behavior) -- Fiction; Sexual dominance and submission -- Fiction; Union Square (New York, N.Y.) -- Fiction; Erotic fiction